2019
DOI: 10.1038/s41598-019-50240-x
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Changes in Synaptic Composition and Astrocytic Involvement in a Mouse Model of Fragile X Syndrome

Abstract: Fragile X Syndrome (FXS), a common inheritable form of intellectual disability, is known to alter neocortical circuits. However, its impact on the diverse synapse types comprising these circuits, or on the involvement of astrocytes, is not well known. We used immunofluorescent array tomography to quantify different synaptic populations and their association with astrocytes in layers 1 through 4 of the adult somatosensory cortex of a FXS mouse model, the FMR1 knockout mouse. The collected multi-channel data con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…Therefore, the present culture system might be particularly well suited for the research of neurodevelopmental disorders both as pure astrocyte as well as in co-culture assays. Astrocytes contribute to impaired neuronal function in many neurodevelopmental disorders [ 59 , 60 , 61 ] and patient-derived astrocyte models can make a significant contribution to studies of human brain function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present culture system might be particularly well suited for the research of neurodevelopmental disorders both as pure astrocyte as well as in co-culture assays. Astrocytes contribute to impaired neuronal function in many neurodevelopmental disorders [ 59 , 60 , 61 ] and patient-derived astrocyte models can make a significant contribution to studies of human brain function.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is a translational repressor that is expressed in both neurons and astrocytes and is vital for normal synaptic transmission between neurons. Many studies on FXS have been conducted to look at the functional role of astrocytes in various processes including synaptic development, synaptic transmission, and dendritic spine morphology (Ariza et al, 2017;Cheng et al, 2012;Simhal et al, 2019). Simhal et al (2019) recently conducted a study in a mice model of FXS to identify the role of astrocytes in synaptic composition.…”
Section: Conditions That Show Astrocytosis and Morphological Changesmentioning
confidence: 99%
“…Many studies on FXS have been conducted to look at the functional role of astrocytes in various processes including synaptic development, synaptic transmission, and dendritic spine morphology (Ariza et al, 2017;Cheng et al, 2012;Simhal et al, 2019). Simhal et al (2019) recently conducted a study in a mice model of FXS to identify the role of astrocytes in synaptic composition. Via immunofluorescent array tomography, they found that in FMRP knockout (KO) mice, there was a significant reduction in the density and amount of excitatory glutamatergic synapses that were associated with the processes of an astrocyte, suggesting that astrocytes have a diminished functional role in the modulation of excitatory synaptic transmission in FXS, consistent with the findings of other similar studies (Jawaid et al, 2018;Simhal et al, 2019).…”
Section: Conditions That Show Astrocytosis and Morphological Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have identified previously unknown features of glial cells that facilitate their interaction with neurons during brain development, such as the release of gliotransmitters and cytokines. In addition, synaptic changes induced by glial cells in the developmental stage, including synaptic patterning secondary to pruning, are now being investigated in relation to the neuron-glia interactions [ 4 , 5 ]. Glial cells release gliotransmitters such as gamma-aminobutyric acid (GABA), glutamate, and cytokines [ 6 , 7 ], which may affect neurons both directly and indirectly [ 8 ].…”
Section: Introductionmentioning
confidence: 99%